Determinants of quality of life and hand function among people with hand osteoarthritis. (9th September 2022) - Pathmanathan, Cinthuja; Deveza, Leticia A.; Robbins, Sarah R.; Duong, Vicky; Venkatesha, Venkatesha; Hunter, David J.
Abstract: Objective: The objectives of this study are to ascertain the determinants of quality of life (QoL) and hand function among persons with hand osteoarthritis (OA) and to assess the influence of hand function on QoL among persons with OA. Methodology: Two hundred and four participants in a clinical trial completed the baseline assessment. Demographic, socioeconomic, QoL (AqoL‐4D), hand function (Functional Index for Hand Osteoarthritis, FIHOA), pain assessment, radiographic and clinical characteristics of participants were measured using standard methods. Univariate and multivariate analyses were performed to evaluate potential associations. Results: We studied 204 participants (76% female, age 65.63 ± 8.13 years, body mass index 28.7 ± 6.5 kg/m 2 ) with hand OA. The mean pain score of the participants on a visual analog scale was 57.8 ( SD ±13.6). There was a significant, negative moderate correlation between hand function and QoL scores except for the sense domain score. Global assessment, household income and serious illness were associated with QoL ( P < .001) and explained 18% of the variance of the QoL. Pain scale, Patient Global Assessment, Mental Health Score, grip strength and cyst index were associated with hand function score and explained 26% of the variance of hand function. Conclusion: The results indicate increasing impairment in hand function decreases the QoL of persons with hand OA. Some determinants were significantly associated with hand function and QoL. Determinants related to hand functions may be modifiable. In future, appropriate intervention strategies should be implemented, and further studies should be conducted to identify the effectiveness of those interventions.